2020
DOI: 10.1186/s12864-020-06847-w
|View full text |Cite
|
Sign up to set email alerts
|

Genomic nucleotide-based distance analysis for delimiting old world monkey derived herpes simplex virus species

Abstract: Background: Herpes simplex viruses form a genus within the alphaherpesvirus subfamily, with three identified viral species isolated from Old World monkeys (OWM); Macacine alphaherpesvirus 1 (McHV-1; herpes B), Cercopithecine alphaherpesvirus 2 (SA8), and Papiine alphaherpesvirus 2 (PaHV-2; herpes papio). Herpes B is endemic to macaques, while PaHV-2 and SA8 appear endemic to baboons. All three viruses are genetically and antigenically similar, with SA8 and PaHV-2 thought to be avirulent in humans, while herpes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…Recently, it was reported that the genetic characteristics, based on genetic markers of mtDNA, Y chromosome genes SRY and TSPY, whole genome sequences, and autosomal SNPs, are very distinctive between these two subspecies [34][35][36][37]. This reflects that each clade of BVs has independently evolved in a specific macaque species/subspecies [38]. This was also confirmed by the bigger picture that M. fascicualris, M. fuscata, and M. mulatta-which belonged to the same species group of fascicularis-were separated from M. nemestrina, which belonged to the silenus-sylvanus group [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the genetic characteristics, based on genetic markers of mtDNA, Y chromosome genes SRY and TSPY, whole genome sequences, and autosomal SNPs, are very distinctive between these two subspecies [34][35][36][37]. This reflects that each clade of BVs has independently evolved in a specific macaque species/subspecies [38]. This was also confirmed by the bigger picture that M. fascicualris, M. fuscata, and M. mulatta-which belonged to the same species group of fascicularis-were separated from M. nemestrina, which belonged to the silenus-sylvanus group [39].…”
Section: Discussionmentioning
confidence: 99%
“…Papiine alphaherpesvirus 2 (PaHV2) is closely related to McHV1 but has not been reported to cause disease in humans [3][4][5]. Herpes simplex viruses (HSV) 1 and 2 are more distant, with HSV2 showing a slightly closer overall relationship to PaHV2 than HSV1 [3,5].…”
Section: Introductionmentioning
confidence: 99%